Socialization of the Use of Cross-sectional Area Variations Container for the Amount of Weight Reduction in Organic Waste by Using BSF Maggots (Black Soldier Fly) - Mila Sari; Kalasta Ayunda; Siti Handam Dewi; Rantika Maida Sahara (Sustainable Applied Modification Evidence Community (SAMEC), 2024)
Organic waste processing is a major challenge in environmental management that requires an effective solution. One promising method is using Black Soldier Fly (BSF) larvae to convert organic waste into high-value biomass. Therefore it is necessary to do itsocialization of the use of variations in the cross-sectional area of ​​containers in cultivating BSF larvae for processing organic waste. The method done ieSocialization to the community includes BSF larvae, life cycle, cultivation procedures and benefits. Results: SSocialization shows an increase in public understanding about cultivating BSF larvae and the influence of variations in the cross-sectional area of ​​containers on waste processing efficiency. Discussion:What happens in the socialization is optimizing the growth conditions for BSF larvae and the obstacles that may occur in cultivating BSF larvae. So thatregulate the water content of BSF Larva feed and maintain the condition of the container. The conclusion of this outreach is increased understanding among the community about the importance of processing organic waste and the role of BSF larvae in reducing waste. So this results in efforts to manage organic waste and create new jobs for the community.